Biohydrogen by Rhodobacter sphaeroides during photo-fermentation: Mixed vs. sole carbon sources enhance bacterial growth and H2 production. (8th January 2019) - Hakobyan, Lilit; Gabrielyan, Lilit; Trchounian, Armen
Abstract: Mixed carbon sources fermentation by bacteria is a promising approach for biohydrogen (H2 ) production biotechnology. In the present study, growth and Н2 production by purple bacteria Rhodobacter sphaeroides MDC6521 during mixed carbon sources (succinate + acetate, succinate + malate, and malate + acetate) photo-fermentation was investigated. The growth rate of bacteria in mixed carbon sources containing medium was of ∼0.33 h −1 which was considerably higher (1.3–1.7-fold) compared with sole carbon substrate containing one. Moreover, the H2 production during photo-fermentation of succinate and acetate mixture was of ∼6.5 mmol H2  g −1 (dry weight of biomass) and significantly more (∼2–3-fold) than that with appropriate sole sources and higher (1.5-fold) than that with succinate and malate mixture. Probably, supplementation of the mixed carbon sources into bacterial culture alters the mode of metabolism, resulting in enhanced H2 production, thus they can be preferable compared to the sole carbon source. The changed FO F1 -ATPase activity of membrane vesicles suggested its important role in the increase of Н2 production efficiency. The results showed that mixed carbon sources provide more H2 than the sole carbon substrates and succinate with acetate mixture is better than succinate with malate. Highlights: R. sphaeroides growth rate was higher in the presence of mixed vs. sole carbon sources. H2 production is enhanced during photo-fermentation of succinate and acetate mixture. The FO F1 -ATPase is involved in the increase of Н2 production.